2001
DOI: 10.1021/es000198n
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Effects of Long-Term Exposure to Bisphenol A in the Fathead Minnow (Pimephales promelas)

Abstract: Bisphenol A (BPA), a high-volume chemical used to make polycarbonate plastic, epoxy resins, and other chemicals has been reported to be weakly estrogenic. To investigate the effects of long-term exposure to Bisphenol A, a multigeneration study was conducted in which fathead minnows (Pimephales promelas) were exposed to water concentrations of BPA in the range from 1 to 1280 micrograms/L. In this paper, we report the growth and reproductive effects of BPA on sexually mature adults in the F0 generation (after 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
156
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(175 citation statements)
references
References 53 publications
16
156
0
1
Order By: Relevance
“…This is in agreement with other studies in which, at this same exposure dose, lesions were observed, with the diameter of some lobules being seen to be reduced and spermatogenesis inhibited (Mandich et al 2007). Also, at 16 µg/l of exposure in fathead minnows, a decrease in the number of mature spermatozoa was elicited (Sohoni et al 2001). This differs from our study since, when carrying out the morphometric analysis of this group (10 µg/l), the only case in which we did observe significant differences (P < 0.05) was in the percentage of spermatids and spermatozoa compared to the groups with the higher concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with other studies in which, at this same exposure dose, lesions were observed, with the diameter of some lobules being seen to be reduced and spermatogenesis inhibited (Mandich et al 2007). Also, at 16 µg/l of exposure in fathead minnows, a decrease in the number of mature spermatozoa was elicited (Sohoni et al 2001). This differs from our study since, when carrying out the morphometric analysis of this group (10 µg/l), the only case in which we did observe significant differences (P < 0.05) was in the percentage of spermatids and spermatozoa compared to the groups with the higher concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…These observations are in contrast to those made in the study of Mandich et al (2007), who, after exposure of carp to the same concentration of BPA, described a reduction in the sperm ducts and the lobule diameter. Similar observations were made in a study on fathead minnows (Pimephales promelas), in which a diminution was observed in the proportion of the different types of cells (an increase in the proportion of spermatocytes) after exposure to 1 µg/l of BPA (Sohoni et al 2001). In contrast, other authors observed cell debris in efferent ducts, germ cells syncytia, granulomas, mineralisation in efferent ducts and sperm necrosis in response to 17-β-oestradiol exposure at a concentration of 2.7 µg/l over the course of 10 days (Wolf et al 2004).…”
Section: Discussionsupporting
confidence: 85%
“…This assumption was made taking in account that this pollutant was never found in all other sampling surveys and, in spite of its rapid degradation levels (Kang and Kondo 2005) there was no accumulation of it in deep waters. Because BPA was identified as a weakly estrogenic substance, with effects on the breeding of some fish species, in concentrations at or higher than 640 μg/L (Sohoni et al 2001;Staples et al 2002) and because the levels measured for BPA in the surface waters of the Mondego estuary (Table 1) were considerably lower than those reported before, it is possible that if endocrine disruption exists in this estuary it is not promoted by the individual contribution of this compound but by the synergetic effect of all chemicals as a whole.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of endocrine disrupting chemicals (EDCs) in the environment has recently become a major issue of concern from the perspectives of both human and ecosystem integrity [1,2,3]. Most of those EDCs have the ability to induce responses similar to those caused by estrogens.…”
Section: Introductionmentioning
confidence: 99%